Forms of innovation inspired by open educational resources: a post-project analysis. (4th May 2019) - Coughlan, Tim; Pitt, Rebecca; Farrow, Robert
ABSTRACT: It has been argued that Open Educational Resources (OER) present opportunities for innovation in education. However, there has been a lack of retrospective analysis of the forms of innovation that can emerge through OER, and the processes and challenges these entail. This paper presents a post-project analysis of the diverse uses and impacts of open courses produced through an international OER initiative. A thematic analysis of retrospective interviews and documentation from this case study is reported on, guided by a review of relevant concepts from innovation and OER literature. Through this we identify three archetypal forms through which the OER created opportunities for innovation: Specific Adoption; Preferred Practise and Foundations for Innovation. We identify drivers and inhibitors through which these forms of innovation interacted with each other in this initiative. This elaborates on the notion that a single existing model does not capture the multi-faceted relationships between innovation and OER.